ANALYSIS OF DIGITAL TAX IMPOSITION BASED ON THE GENERAL AGREEMENT ON TRADE IN SERVICES - Anugrah Adiastuti; Siti Muslimah; Sekar Poetry Mahardhika (DE'RECHTSSTAAT, 2024)
Trade liberalization has consequences with the opening of global market access widely.. Along with the development of the era, international trade activities have begun to move towards the digital economy, one of which is reflected in the practice of digital multinational companies (digital MNEs). State revenue with the potential of the digital economy has also increased, where in 2023 the value of Indonesia's digital economy will reach US$82 billion. This study aims to identify the implementation of digital taxation on digital multinational companies in terms of GATS provisions. This paper uses a prescriptive legal research method using a statutory approach which in this case examines legal regulations relating to the imposition of digital taxes in international trade practices. The results of the study indicate that the imposition of digital taxes on multinational companies as per the concept of the Two Pillars of Tax Policy can be classified as a form of NTB. However, if the digital taxation policy that will be implemented in Indonesia has been adjusted to the idea of ​​the OECD Two Pillars of Tax Policy Concept, it is hoped that it will not conflict with the rules or principles of international trade, especially in GATS.